Pharmacokinetics of a new once‐daily controlled‐release sarpogrelate hydrochloride compared with immediate‐release formulation and the effect of food. (11th December 2013) - Kim, T.‐E.; Kim, J.‐R.; Jung, J. A.; Kim, M.‐J.; Lee, S.‐Y.; Ko, J.‐W.; Jung, W.‐T.; Choi, Y.‐W.; Lee, H. J.; Kim, S.‐H.; Huh, W.
Summary What is known and objective Sarpogrelate is a selective 5‐hydroxytryptamine receptor subtype 2A antagonist that inhibits platelet aggregation and vasoconstriction. The aim of this study was to compare the pharmacokinetics of a sarpogrelate controlled‐release formulation (CR) with those of the immediate‐release formulation (IR). The effect of food on the pharmacokinetics of CR sarpogrelate was also evaluated. Methods A randomized, open‐label, 3‐period, 3‐treatment crossover study was conducted in 50 healthy male subjects. Subjects were allocated into one of six sequence groups. In one period, a 100‐mg IR formulation was administered three times at 6‐h intervals, and in the other two periods, a 300‐mg CR formulation was administered once to fasting and once to fed subjects. Each period was separated by a 7‐day washout period. Serial blood samples were collected up to 24 h after the first drug administration in each period. The plasma concentrations of sarpogrelate were analysed by liquid chromatography–tandem mass spectrometry. Pharmacokinetic parameters were calculated by non‐compartmental methods. Results and discussion After the administration of the IR formulation, the plasma concentration reached a peak at 0·48 h and the drug was eliminated with a half‐life (t1/2) of 0·7 h. After administration of the CR formulation, the plasma concentration reached a peak at 0·5 h and the drug was eliminated with a t1/2 of 3·23 h. The geometric mean ratios (CR/IR) for sarpogrelate area under the plasma concentration–time curve (AUC) and the maximum plasma drug concentration (Cmax) were 1·2040 (90% confidence interval (CI): 1·0992–1·3188) and 0·9462 (90% CI: 0·8504–1·0529). When CR was administered to fed subjects, the time to peak concentration was prolonged to 3·97 h and t1/2 was shortened to 1·45 h. The geometric mean ratios (fasting/fed) for sarpogrelate AUC and Cmax were 0·8573 (90% CI: 0·7687–0·9561) and 0·6452 (90% CI: 0·5671–0·7341). What is new and conclusion After the administration of CR and IR formulations of the same daily dose of sarpogrelate hydrochloride, the overall systemic exposure was slightly higher for the CR than for the IR formulation, whereas peak concentration was comparable between the two formulations. Food reduced the bioavailability of sarpogrelate CR.